Pedagogical Use of Interactive Flat Panels in Teaching English: A Classroom- Based Study at Senior High School - Syafaruddin Marpaung; Rahmah Fithriani; Saiful Anwar Matondang; Amirul Mukminin (Jurnal Ragam Pengabdian, 2026)
The use of digital technology in English language learning is becoming increasingly important to improve student engagement and learning quality. However, the use of Interactive Flat Panels (IFPs) in English classes has not always been accompanied by optimal pedagogical use. This study aims to analyze the pedagogical use of Interactive Flat Panels in English language learning at the senior high school level, identify their pedagogical benefits, and reveal the obstacles faced by teachers in their implementation. This study uses a qualitative approach with a classroom-based study design. Data were collected through learning observations, interviews with English teachers, and documentation of learning activities. The results show that IFPs are used to display video materials, presentations, listening exercises, and digital-based interactive games that increase student participation and engagement. However, limited technical understanding and the need for repeated training are major challenges for teachers. This study concludes that effective use of IFPs requires teachers' pedagogical readiness and support for continuous professional development.